Molecular docking and acetylcholinesterase inhibitory activity of psoralen derivatives - Kamarudin, Natasha Amira (2020)
Alzheimer Disease (AD) is a deadly neurodegenerative disease which cause irreversible memory loss and progressive cognitive dysfunction, together with impaired language skill and personality changes. Even though the exact cause of AD is not fully understood, some factors such as low levels of neurotransmitter acetylcholine (ACh) is believed to play a vital role in the progress of AD. Hence, the most promising method for the treatment of AD is to increase the levels of ACh in the brain by inhibiting the acetylcholinesterase (AChE) enzyme. However, due to the complex nature of AD, standard drugs with AChE inhibitors such as galanthamine, donepezil, rivastigmine and tacrine can only alleviate the symptoms but cannot cure neurodegeneration. Thus, it is significant to develop multifunctional drugs which are Multi-Target Directed Ligands (MTDLs) as the best approach for the treatment of AD. Based on previous studies, coumarin derivatives possess a wide range of biological activities such as a potent AChE inhibitor. Thus, the objectives of this study are to carry in silico evaluation of the extracted AChE protein and perform molecular docking of psoralen derivatives which is also known as furocoumarin, with AChE protein. Acetylcholinesterase inhibitory activity of psoralen derivatives was also conducted. Results from molecular docking shows potential of compound (21) as AChE inhibitors due to its highest binding energy value. It was further supported by the result from acetylcholinesterase inhibitor activity, whereby compound (21) has 91.69% inhibition which is comparable to galantamine (94.12%).